2020
DOI: 10.1111/coin.12422
|View full text |Cite
|
Sign up to set email alerts
|

Classifying and clustering malicious advertisement uniform resource locators using deep learning

Abstract: Malicious online advertisement detection has attracted increasing attention in recent years in both academia and industry. The existing advertising blocking systems are vulnerable to the evolution of new attacks and can cause time latency issues by analyzing web content or querying remote servers. This article proposes a lightweight detection system for advertisement Uniform resource locators (URLs) detection, depending only on lexical-based features. Deep learning algorithms are used for online advertising cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The framework was also inadequate in demonstrating the correlation that exists among those features extracted; thus, it cannot identify emerging Android malware. Using t-distribution stochastic neighbor embedding (t-SNE) for visualization, Zhang et al [58] proposed a method for detecting malicious adverts in addresses of web pages using lexical-based features. Even though HTTPs provide authentication on the web browsers and pages to offer data secrecy [59], the study of Barrera et al [60] demonstrated that sophisticated malware leverage on permission-based security vulnerabilities to infect Android and web-based applications.…”
Section: Bayesian Correlation Opcode Sequence and T-distribution Stoc...mentioning
confidence: 99%
“…The framework was also inadequate in demonstrating the correlation that exists among those features extracted; thus, it cannot identify emerging Android malware. Using t-distribution stochastic neighbor embedding (t-SNE) for visualization, Zhang et al [58] proposed a method for detecting malicious adverts in addresses of web pages using lexical-based features. Even though HTTPs provide authentication on the web browsers and pages to offer data secrecy [59], the study of Barrera et al [60] demonstrated that sophisticated malware leverage on permission-based security vulnerabilities to infect Android and web-based applications.…”
Section: Bayesian Correlation Opcode Sequence and T-distribution Stoc...mentioning
confidence: 99%